‘ADA AQUA’ CAMPAIGN AND THE RISK OF DEHYDRATION: CIRCUIT-OF-CULTURE MODEL - Windasari Gayuh Mardatilah; Abhirama S.D. Perdana (President University, 2018)
AQUA as the pioneering bottled water industry in Indonesia created the Ada AQUA Campaign.Ada AQUA Campaign is an informational campaign promoting adequate water consumption to preventdehydration that can cause lack of concentration. Ada AQUA Campaign was held as a strategic move to securethe future growth of AQUA. This research analyses how Ada AQUA Campaign is produced, circulated andconsumed by people especially young people in Indonesia and then achieve its goal through Social NetworkingSites (SNS) or three main social media, such as Twitter, Instagram, and Facebook. The competition amongbottled water company in Indonesia is getting competitive. Ada AQUA Campaign has received good responsesfrom a lot of people. It can be seen through the use of the hashtag #AdaAQUA in SNS. AQUA has encouragedIndonesian especially young people to join and participate in Ada AQUA Campaign. This campaign targeted50,000 mentions and reached 450,000 mentions for the hashtag #AdaAQUA. Ada AQUA Campaign became thesuccessful campaign that AQUA ever held. The gap in this research is that there are still a few researcher andpublic relations practitioner who use Circuit of Culture to analyse cultural experience. This research willcontribute to the literature or journal of international public relations. Linking to the new media, this research isusing Circuit of Culture as a framework to explain each moment and dig the understanding of how Ada AQUACampaign is produced, circulated, and consumed by people especially young people in Indonesia.